Bioavailability of anthocyanins. (November 2014) - Fang, Jim
Abstract Anthocyanins are a subgroup of flavonoids responsible for the blue, purple, and red color of many fruits, flowers, and leaves. Consumption of foods rich in anthocyanins has been associated with a reduced risk of cardiovascular disease and cancer. The fate of anthocyanins after oral administration follows a unique pattern rather different from those of other flavonoids. Anthocyanins could be absorbed from the stomach as well as intestines. Active transporters may play a role in the absorption of anthocyanins from the stomach as well as in their transfer within the kidney or liver. Anthocyanins such as cyanidin-3-glucoside and pelargonidin-3-glucoside could be absorbed in their intact form into the gastrointestinal wall; undergo extensive first-pass metabolism; and enter the systemic circulation as metabolites. Phenolic acid metabolites were found in the blood stream in much higher concentrations than their parent compounds. These metabolites could be responsible for the health benefits associated with anthocyanins. Some anthocyanins can reach the large intestine in significant amounts and undergo decomposition catalyzed by microbiota. In turn, these decomposition products may contribute to the health effects associated with anthocyanins in the large intestine. This review comprehensively summarizes the existing knowledge about absorption, distribution, metabolism, and elimination of anthocyanins as well as their decomposition within the gastrointestinal lumen.